Rehabilitation of irrigation systems in Sri Lanka: a literature review - Abeysekera, W.A.T. (International Irrigation Management Institute, 1993)
The purpose of this literature review is to identify the lessons learnt from the implementation of these projects based on available literature, and the gaps that need to be filled by additional research. It brings out clearly a number of lessons learned, some of which have been incorporated in recent projects, and some not. Many of these lessons are applicable not only to Sri Lanka but more widely. The lessons include: the importance of involving farmers from the begining and using the improvment process to build farmer's organizations; the effectiveness of specially trained catalysts for organizing farmers; the imporatnce of addressing agricultural, technological, marketing, and other issues as well as irrigation problems; and the necessity to build in better monitoring and evaluation processes.